Usefulness of contrast‐enhanced ultrasonography using Sonazoid for the assessment of therapeutic response to percutaneous radiofrequency ablation for hepatocellular carcinoma. Issue 4 (27th June 2014) - Nishigaki, Yoichi; Hayashi, Hideki; Tomita, Eiichi; Suzuki, Yusuke; Watanabe, Naoki; Watanabe, Satoshi; Watanabe, Chiaki; Takagi, Yui; Kato, Tomohiro; Naiki, Takafumi
<x xml:space="preserve">Abstract</x> Aim Accurate assessment of the coagulated area is imperative to achieve an excellent outcome from percutaneous radiofrequency ablation (PRFA) for the treatment of hepatocellular carcinoma (HCC). We evaluated the efficacy of contrast‐enhanced ultrasonography (CEUS) with the contrast‐enhancing agent Sonazoid for precisely assessing the therapeutic effect of PRFA for HCC. Methods We enrolled 87 consecutive patients with solitary naïve HCC of less than 3 cm in diameter. PRFA treatment was performed with a 17‐G cool‐tip needle, and CEUS was performed to assess the ablative margin 3 h after the procedure, when the coagulated tumor outline was easiest to discern. The treatment was repeated until an ablative margin greater than 5 mm was confirmed. After CEUS assessment of the therapeutic response, the patients were followed to investigate local tumor recurrence. Results In 78 patients (89.7%), the outline of the coagulated tumors could be recognized by ultrasonography, and CEUS assessment of the ablative margin was successful. The remaining nine patients were assessed by computed tomography. The 5‐year cumulative survival rate after the assessment of the treatment response with CEUS was 58.4%, and the 4‐year cumulative total recurrence rate was 72.3%. The 5‐year cumulative local tumor recurrence rate was very low (2.3%). Conclusion The assessment with CEUS at 3 h after the PRFA procedure was successful in the majority of the patients, and it yielded a very low rate of local recurrence.